THE IMPORTANCE OF NEEDS ANALYSIS IN CURRICULUM DEVELOPMENT FOR ESL/EFL CLASSROOM - Amalul Umam (ENGLISH, 2016)
West (1994) states that needs analysis (NA) is what learners will be required to do with the foreign language in the target situation, and how learners might best master the target language during the period of training. There are a lot of studies that proved that NA has important role in the development of a curriculum. This study will try to discuss the importance of NA in curriculum development for ESL/EFL classroom. The history of curriculum development and its emergence in language teaching will be discussed. Some syllabuses will be explained from which ELT practitioners can have some pictures of materials and the learning process in ELT classrooms.